The Mediating Role of Religiosity on the Big Five Personalities and Marital Satisfaction in Indonesia: A Perspective of Da'wah Psychology - Bukhari Bukhari; Shovia Lintina; Sabiruddin Sabiruddin; Mistarija Mistarija; A’dawiyah Ismail; Septin Maisharah K (Islamic Guidance and Counseling Journal, 2023)
Personality and religiosity have been found to be the most important predictors of marital satisfaction in empirical studies. However, there has not yet been any research that examines the causal relationship between personality and religiosity and the impact of both on marital satisfaction in the same model, from the perspective of da'wah psychology. In the current study, we aimed to verify the relationship between personality and marital satisfaction is mediated by religiosity, as it is perceived as motivation from the perspective da’wah of psychology. This research uses a quantitative approach, and statistical analysis methods in path analysis research using Mplus software version 8.0. The sample consisted of 347 participants. The results show that 1) Personality type affects marital satisfaction mediated by religiosity fit with data significantly and negatively and 2) Negative personality emotionality affects marital satisfaction both directly and through religiosity as a mediator variable, where religiosity is as a partial mediator. The perspective of da'wah psychology is an approach that integrates religious principles with psychological knowledge so that it can provide a deeper understanding of helping individuals develop their potential and improve the quality of their lives and provide a framework for understanding the role of religiosity by emphasizing the importance of applying religious values in shaping marital satisfaction. The implications of this study highlight the importance of religiosity as a mediator in overcoming problems and suppressing negative emotionality so as to increase marital satisfaction in each couple within the framework of da'wah psychology.